Strategi Efektif dalam Meningkatkan Kualitas Pembelajaran Al-Qur’an di TPQ Darul Ulum Desa Kreyo Wonotunggal Batang - Uzli Fatuddiniyah; Sholahuddin Sholahuddin; Alfika Alfika; Anriev Tsabat Kautsar Inmay; Nurul Khasanah; Pradipta Kurniasanti (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
Education is a systematic and continuous process for developing a person's knowledge, skills, attitudes and values. The main goal of education is to prepare individuals to function effectively in society, as well as to facilitate personal growth and development. One of these is the Al-Qur'an Education Park. The Al-Qur'an Education Park (TPQ) has an important role in children's religious education, but often faces challenges in terms of improving the quality of teaching. This article discusses various effective strategies that can be implemented to improve the quality of teaching at TPQ Darul Ulum . This research also explores the role of technology in supporting the teaching and learning process and the importance of parental involvement in supporting children's learning. The research results show that strategies such as continuous training for teachers, use of interactive learning media, and regular evaluations have a positive impact in increasing the effectiveness of teaching at TPQ. It is hoped that this article can serve as a guide for TPQ administrators to implement best practices and achieve higher educational standards within the TPQ environment